Evaluation of English Language Question Papers for Content Validity at Intermediate Level: A Case Study of Board of Intermediate and Secondary Education, Sukkur - Ikramullah Khan (University of Chitral Journal of Linguistics and Literature)
The purpose of this study was to examine if the annual English exam question papers of first year accurately reflected the synchronisation of the National Curriculum Benchmarks (2006) with the questions on the test administered by the Board of Intermediate and Secondary Education Sukkur. Annual question papers from BISE Sukkur's XI courses were chosen to examine content validity across a five-year period (2014-18). A survey questionnaire was used to obtain data from ELT experts. When compared to the Benchmarks of the National Curriculum of English Language (2006), the data revealed that the items on the annual question papers had very low content validity. The study recommends some effective ways for developing effective question papers aligned with Benchmarks.